Diálogo inter-religioso e dignidade humana: contribuições do pontificado de Francisco - 2013 a 2017. - Melo, Maria Graciane Clemente de (2019)
This dissertation aims to analyze, from the Pope Francis’ speeches between 2013 and 2017, the engagement of religions in the pursuit of human dignity. The dialogue category finds resonance at the present moment, especially by the growing demonstrations of intolerance and mistrust with those who have adopted a different faith from the hegemonic ones. This picture reaches the school space, given the fact that the school is a fertile field for reflection on the diversity of roles played socially. For the methodological course, we first analyzed the category Dialogue, from the perspective of Paulo Freire, in the search for contributions that this category could bring to the Sciences of Religion. Afterwards, we conducted the documentary analysis of Pope Francis’ speeches, during the most diverse meetings, whether in the Vatican or in pastoral visits, between the year of his election (2013) and 2017, totaling the first 5 years of his papacy, considering that this would be a reasonable time to identify points of congruence about their defense of interreligious dialogue.